Workshop on community-based household organic waste management using ThrowbinC at the Aisyiyah Kampung Dadap Medan Organization - Gina Cynthia Raphita Hasibuan; Tania Alda; Nisaul Fadilah Dalimunthe; M. Thoriq Al Fath; Salwa Afifah; Juan Akmal Nasution; Janeta Fazriah Rambe; Indah Mutya Sari (ABDI SABHA (Jurnal Pengabdian kepada Masyarakat), 2022)
Nancy Y. Disasters Due to Garbage, Floods and Landslides [Internet]. 2021 [cited 2022 Feb 8]. Available from: https://tirto.id/bencana-hasil-sampah-gunung- until-longsor-sampah-gaB Z Wardhana AH. Black Soldier Fly (Hermetia illucens) as an Alternative Protein Source for Animal Feed. WARZOA. 2016;26(2):69–78. United Nations Goal 12 | Department of Economic and Social Affairs [Internet]. [cited 2022 Feb 12]. Available from: https://sdgs.un.org/goals/goal12 SIPSN. SIPSN - National Waste Management Information System [Internet]. 2021 [cited 2022 Jan 25]. Available from: https://sipsn.menlhk.go.id/sipsn / i?ková H, Newton GL, Lacy RC, Kozánek M. The use of fly larvae for organic waste treatment. Waste Manag. 2015 Jan 1:35:68–80. Rindhe SN, Chatli MK, Wagh RV, Kaur A, Mehta N, Kumar P, et al. Black Soldier Fly: A New Vista for Waste Management and Animal Feed. Int J Curr Microbiol Appl Sci. 2019 Jan 20;8(01):1329–42. Diener S, Studt Solano NM, Roa Gutiérrez F, Zurbrügg C, Tockner K. Biological treatment of municipal organic waste using black soldier fly larvae. Waste and Biomass Valorization [Internet]. 2011 Nov 18 [cited 2022 Jan 28];2(4):357–63. Available from: https://link.springer.com/article/10.1007/s12649-011-9079-1 Supriyatna A, Kurahman OT, Cahyanto T, Yuliawati A, Kulsum Y, Supriyatna A, et al. The Potency of Black Soldier Larvae (Hermetia illucens L.) as a Source of Protein for Livestock Feed. Bioscientific J Biol Biol Educ [Internet]. 2018 Aug 29 [cited 2022 Jan 28];10(2):448–54. Available from: https://journal.unnes.ac.id/nju/index.php/biosaintifika/article/view/14422 Liu T, Awasthi MK, Chen H, Duan Y, Awasthi SK, Zhang Z. Performance of black soldier fly larvae (Diptera: Stratiomyidae) for manure composting and production of cleaner compost. J Environment Manage. 2019 Dec 1:251:109593.